Impact of case management (Evercare) on frail elderly patients: controlled before and after analysis of quantitative outcome data. Issue 7583 (15th November 2006) - Gravelle, Hugh; Dusheiko, Mark; Sheaff, Rod; Sargent, Penny; Boaden, Ruth; Pickard, Susan; Parker, Stuart; Roland, Martin
Abstract : Objectives To determine the impact on outcomes in patients of the Evercare approach to case management of elderly people. Design Practice level before and after analysis of hospital admissions data with control group. Setting Nine primary care trusts in England that, in 2003-5, piloted case management of elderly people selected as being at high risk of emergency admission. Main outcome measures Rates of emergency admission, emergency bed days, and mortality from April 2001 to March 2005 in 62 Evercare practices and 6960-7695 control practices in England (depending on the analysis being carried out). Results The intervention had no significant effect on rates of emergency admission (increase 16.5%, (95% confidence interval −5.7% to 38.7%), emergency bed days (increase 19.0%, −5.3% to 43.2%), and mortality (increase 34.4%, −1.7% to 70.3%) for a high risk population aged >65 with a history of two or more emergency admissions in the preceding 13 months. For the general population aged ≥65 effects on the rates of emergency admission (increase 2.5%, −2.1% to 7.0%), emergency bed days (decrease −4.9%, −10.8% to 1.0%), and mortality (increase 5.5%, −3.5% to 14.5%) were also non-significant. Conclusions Case management of frail elderly people introduced an additional range of services into primary care without an associated reduction in hospital admissions. This may have been because of identification of additional cases. Employment of community matrons is now a key feature of case management policy in the NHS in England. Without more radical system redesign this policy is unlikely to reduce hospital admissions.